2019
DOI: 10.1038/s41598-019-43295-3
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-Related Alterations in Airway Gene Expression are Rapidly Reversed Within Weeks Following Smoking-Cessation

Abstract: The physiologic response to tobacco smoke can be measured by gene-expression profiling of the airway epithelium. Temporal resolution of kinetics of gene-expression alterations upon smoking-cessation might delineate distinct biological processes that are activated during recovery from tobacco smoke exposure. Using whole genome gene-expression profiling of individuals initiating a smoking-cessation attempt, we sought to characterize the kinetics of gene-expression alterations in response to short-term smoking-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…We adopted previous approaches to show that IEGs may potentially quantify and predict harmful effects in humans, known as biomarkers of potential harm, based on the magnitude and direction of expression 140–142. Furthermore, IEG testing in the nasal epithelium and gingiva (the gums) is a promising and non-invasive alternative with clinical relevance 143 144. These results emphasise the importance of policies that support the research and development of IEGs as novel non-traditional biomarkers of newly modified tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted previous approaches to show that IEGs may potentially quantify and predict harmful effects in humans, known as biomarkers of potential harm, based on the magnitude and direction of expression 140–142. Furthermore, IEG testing in the nasal epithelium and gingiva (the gums) is a promising and non-invasive alternative with clinical relevance 143 144. These results emphasise the importance of policies that support the research and development of IEGs as novel non-traditional biomarkers of newly modified tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analysis of lung epithelium gene expression has shown that whereas most smoking-related changes reverse following smoking cessation, some appear to be permanent, even in long-term former smokers [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…GSEA used datasets analyzing airway epithelial cells from patients exposed to cigarette smoke for 30 minutes four times (GSE30660) before gene expression analysis and bronchial epithelium air-liquid interface (ALI) cultures exposed cigarette smoke for 24 hours before gene expression analysis (GSE82137) (21). We conducted GSVA on a dataset that analyzed nasal epithelium gene expression from smokers who had quit smoking, over a 6-month period (GSE83364) (22). We also conducted GSVA on datasets that analyzed changes gene expression in A549 cells in which NRF2 (GSE113519) and AHR (GSE109576) (23) are inhibited.…”
Section: Gene Expression Profiling and Mapping With In Vitro Datasetsmentioning
confidence: 99%
“…To explore the effect of smoking cessation on genes that change with smoke exposure, we performed a GSVA using an independent in vivo nasal smoking cessation dataset (22). A subset of the 25 top significantly increased and a second subset of the 25 top significantly decreased genes in the nasal epithelium were analyzed for changes associated with smoking cessation.…”
Section: Gene Expression Levels Reverse With Smoking Cessationmentioning
confidence: 99%